Bio-inspired sensing and actuating materials. Issue 22 (10th May 2019) - Zhao, Qilong; Wang, Yunlong; Cui, Huanqing; Du, Xuemin
Abstract : Biological systems contain various amazing examples that can display adaptive and active behaviors in response to external stimuli. Abstract : Biological systems contain various amazing examples that can display adaptive and active behaviors in response to external stimuli. The changes in skin color and/or shapes according to environmental changes are common examples of the adaptive and active behaviors of creatures for better survival. To mimic these outstanding sensing and actuating behaviors of creatures, a new generation of bio-inspired sensing and actuating materials have been recently attracting extensive attention. Based on stimuli-responsive materials, these bio-inspired sensing and actuating materials can also exhibit the capabilities of changing their colors and/or shapes upon exposure to specific external stimuli, which hold great promise in a variety of fields such as sensors, actuators, flexible electronics, soft robotics and various biomedical applications. This review summarizes the-state-of-the-art progress of bio-inspired sensing and actuating materials, with focuses on the design principles and the technologies for forming these materials, as well as the introduction of their potential for versatile applications. Finally, an outlook on the challenges and future directions of bio-inspired sensing and actuating materials is presented.